Problems of production and use of hydroponic products in agricultural production - Bulgakov, Volodymyr; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2019)
Production of hydroponic green fodder is an important task of agriculture, which in developed countries is given enough attention. Currently, the world's developed a considerable number of various designs installations for the production of hydroponic products, but the main working body of these installations are trays in which the cultivation of hydroponic green fodder, as one of the most simple, but fairly effective devices for seeding, cultivation and the ready products. The main global trends in the production of hydroponic green fodder, as one of the components of the diet of poultry and cattle, are considered. The paper analyzes the operation of the workshops for the production of hydroponic products equipped with the facilities of the new design developed by us. Compared some economic characteristics of hydroponic workshops manufactured in foreign countries and developed in Ukraine. Thus, the conclusion is obvious – domestic plants for the production of hydroponic green fodder are more economical than their foreign counterparts.
Keywords: beet tops; cleaning; continuous cut; experimental studies